EVOLUTION OF VLAN - Manisha Barse; Rodney Manuel (International Journal of Innovations in Engineering Research and Technology, 2021)
Enterprise networks are large and complex and their designs must be frequently altered to adapt to changing organizational needs. The process of redesigning and reconfiguring enterprise networks is ad-hoc and error-prone, and configuration errors could cause serious issues such as network outages. Earlier, a Local Area Network (LAN) was defined as a network of computers located within the same area. Today, they are defined as a single broadcast domain. In this paper, we take a step towards systematic evolution of network designs in the context of virtual local area networks (VLANs).We focus on VLANs giving their importance and prevalence, the frequent need to change LAN designs, and the time-consuming and error-prone process of making changes. A virtual LAN, commonlyknown as VLAN, is a group of networking devices in the same broadcast domain logically. A VLAN is a group of hosts with a common set of requirements that communicate as if they were attached to the same wire, regardless of their physical location.